WEBSITE RANKING ESTIMATION THROUGH FUZZY LOGICAL HIERARCHY PROCESS - Katete, Rodrick Symon; Rajendran, Rajamuthu; sankar, Ravi; Kalonga, Given (Universitas Negeri Semarang, 2020)
The purpose of this paper is to provide case study on website evaluation and ranking by fuzzy analytic hierarchy process (FAHP). Many people have misconception about website evaluation and ranking mistaking good design and user interface alone as high ranking. To measure the website quality, various factors are taken into consideration. The quality metrics that are considered for evaluating website are accessibility, performance, usability, search engine optimization (SEO), website visibility, security, technology and design used for developing website. Analytic hierarchy process (AHP) breaks down complexity into simple hierarchical decision making methods. Fuzzy AHP is a multi-purpose judgement technique which is often used to guide website creation and can further be used to find out website ranking. This approach tells the ranking of website based on multiple conflicting criteria of the website. But all these parameters and metrics considered are qualitative and not measurable which is slight challenging to deal with traditional theory. The drawbacks of AHP is eliminated by use of FAHP. Here, fuzzy decision matrix is constructed by using multi-criteria decision making (MCDM) approach and final weight is calculated of each website based on their qualities.